Variational Iteration Method for Generalized Pantograph Equation with Convergence Analysis - Alipour, Mohsen; Baleanu, Dumitru; Karimi, Kobra; Kumar, Sunil (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we solve generalized pantograph equation by changing the problem to a system of ordinary equations and using the variational iteration method. We discuss convergence of the proposed method to the exact solution. Finally, illustrative examples are given to demonstrate the efficiency of the method.